THE IMPACT OF INFORMATION SERVICES THROUGH WHATSAPP MOTIVATION OF CLASS X STUDENTS OF SMAN 3 SAMARINDA IN THE PANDEMIC PERIOD OF THE 2020/2021 ACADEMIC YEAR - Carolina Trianita Tabut; Masnurimma Heriansyah; Andi Wahyu Irawan (Educational Studies: Conference Series, 2021)
The background of this research is due to a decrease in students' learning motivation during the pandemic so that BK teachers provide information services with the help of Whatsapp Group media to increase students' learning motivation during the pandemic. The formulation of the research problem is how the impact of information services through Whatsapp Group in increasing the learning motivation of class X SMA Negeri 3 Samarinda students with the aim of knowing the impact of information services through Whatsapp Group in increasing the learning motivation of class X students of SMA Negeri 3 Samarinda during the pandemic. The type of data used is quantitative research with ex post facto correlational design research methods. The population is all students of class X in SMA Negeri 3 Samarinda with a sample of 138 respondents, purposive sampling technique. Data collection techniques are questionnaires on information services and students' learning motivation. The instrument validity test used the Pearson Product Moment correlation formula, and the instrument reliability test used the Cronbach Alpha coefficient approach reliability index calculation using the SPSS 25 program. The data analysis technique used descriptive analysis and simple linear regression analysis. Before testing the hypothesis, the analysis requirements test was conducted, namely normality and linearity tests using the SPSS 25 program. The results of the research from information services had an average of 132, a frequency of 60% with a useful category and learning motivation in the medium category had an average of 195, a frequency of 71%. In the results of tcount 10.253 > ttable 1.97756, a significance level of 5% means that information services through the Whatsapp Group media have a significant impact on increasing students' learning motivation during the pandemic with an R Square of 44% being in the strong category. This shows that information services through Whatsapp Group can be used as a strategy in increasing students' learning motivation, especially during this pandemic. This research is expected to be used as a reference and reference material to further innovate in providing information services to students' learning motivation.